Strategies to Improve Outcomes of Bullous Pemphigoid: A Comprehensive Review of Clinical Presentations, Diagnosis, and Patients’ Assessment - Ruggiero A; Megna M; Villani A; Comune R; Fabbrocini G; di Vico F (Dove Medical Press, 2022)
Angelo Ruggiero,1 Matteo Megna,1 Alessia Villani,1 Rosita Comune,2 Gabriella Fabbrocini,1 Francesca di Vico1 1Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, 80131, Italy; 2Section of Radiology and Radiotherapy, Department of Precision Medicine, University of Campania Luigi Vanvitelli, Naples, 80138, ItalyCorrespondence: Angelo Ruggiero, Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 081 7462457, Fax +39 081 7462442, Email angeloruggiero1993@libero.itAbstract: Bullous pemphigoid (BP) is the most frequent autoimmune bullous disease mainly affecting elderlies. Diagnosis usually results from clinical features, histological examination, and the quantification of circulating typical autoantibodies, due to its higher incidence in elderly patients, bullous pemphigoid treatment and management still represents a challenge due to the higher frequency of several comorbidities in this group of patients, which may also be linked to a reduced tolerance to BP treatments. Hence, an early diagnosis and a prompt correct treatment are mandatory to reach better clinical outcomes and improve as much as possible BP outcomes. Herein, we carried out a comprehensive literature review about the known clinical presentations, diagnosis, assessment and monitoring procedures used in daily clinical practice in patients with BP, to better define strategies to improve as much as possible BP clinical outcomes.Keywords: bullous pemphigoid, pemphigoid, review, monitoring, assessment, prognosis